When Race, Rape, and Religion Collide - Evelyn Parker (African Journal of Gender and Religion (AJGR))
UN Women identified gender-based Violence (GBV) as the shadow pandemic of the COVID-19 pandemic between 2020 and 2022. For almost two years, women and girls worldwide were sheltering in homes with abusive intimate partners and experiencing violent trauma and even death. The United States (US) was among the nations that experienced lockdown-related spikes in GBV. Indeed, the Centers for Disease Control and Prevention (CDC) reports that the domestic violence crisis peaked in early 2021 during the COVID-19 lockdown, mostly among women and children who were having to shelter with their abusers. Among this population of women living in the US who were experiencing the shadow pandemic were female college/university students who experienced either intimate partner violence (IPV) while sheltering with abusive partners and/or cyber intimate partner aggression (IPA) via technology and social media. Black female college students were not only victims of IPV and IPA but also of femicide during the COVID-19 pandemic. Using a case study of an HBCU chaplain, this article explores intervention in and prevention of IPV, IPA, and femicide during the COVID-19 pandemic at the intersection of race, gender, class, and religion for African-descended female college students. Specifically, this article will investigate what role historical black college/university (HBCU) chaplains play in intervening in lockdown IPV, IPA, and femicide. Using the concept of positionality, the author argues that the HBCU chaplain is a key on-campus figure who can intervene and prevent sexual assault on college and university campuses. The article concludes with suggestions for necessary further research needed to address GBV on HBCU campuses.